Kazakh National Songs (Zhyrlar) as Spiritual Heritage of The Kazakh Nation - Tokzhanov, Tolepbergen; Kudaibergenova, Saltanat; Nurymbetov, Erkin; Igilik, B ayan; Medeubek, Maksat (International Journal of Psychosocial Rehabilitation, 2020)
Studies of Kazakh musical art associated with both folklore and composer creativity, form one of the vast areas of musicology of the XX - XXI centuries.In the scientific works of scientists of different years the issues of the formation of composer creativity in Republic over the past century.The traditional musical culture of the Syr Darya River has not been thoroughly studied. In particular, there are many mysteries in the ancient tradition of singing the epic with loud voices, preserved in Kazakhstan only in this region. The transmission of tradition from the teacher to the student, her mastery can be only exaggerated. Only the so-called "contact" method of communication is able to transmit all the information and musical meanings of the tradition.